a.)\(x = t\)

\(y =\ −4x\ +\ 1\) substituting\(x\ −\ y =\ −4(t)\ +\ 1\)

\(y =\ −4t\ +\ 1\) Hence parametric equations are: \(y =\ −4t\ +\ 1\ and\ x = t\) b.)\(x =\ \frac{t}{2}\)

\(y =\ −4x\ +\ 1\) substituting x: \(y =\ −4(\frac{t}{2})\ +\ 1y =\ −2t\ +\ 1\) hence the parametric equations are: \(y =\ −2t\ +\ 1x =\ \frac{t}{2}\) Step 2 c.)\(x =\ −4t\)

\(y =\ −4x\ +\ 1\) substituting x: \(y =\ −4(−4t)\ +\ 1y = 16t\ +\ 1\) Hence parametric equation are: \(y = 16t\ +\ 1x =\ −4t\)

\(y =\ −4x\ +\ 1\) substituting\(x\ −\ y =\ −4(t)\ +\ 1\)

\(y =\ −4t\ +\ 1\) Hence parametric equations are: \(y =\ −4t\ +\ 1\ and\ x = t\) b.)\(x =\ \frac{t}{2}\)

\(y =\ −4x\ +\ 1\) substituting x: \(y =\ −4(\frac{t}{2})\ +\ 1y =\ −2t\ +\ 1\) hence the parametric equations are: \(y =\ −2t\ +\ 1x =\ \frac{t}{2}\) Step 2 c.)\(x =\ −4t\)

\(y =\ −4x\ +\ 1\) substituting x: \(y =\ −4(−4t)\ +\ 1y = 16t\ +\ 1\) Hence parametric equation are: \(y = 16t\ +\ 1x =\ −4t\)